A formação e o apoio da gestão no sucesso dos ERP - Bento, Fernando (2019)
Bento, F., Costa, C. J., & Aparicio, M. (2019). A formação e o apoio da gestão no sucesso dos ERP. In R. Goncalves, I. Pedrosa, M. P. Cota, & A. Rocha (Eds.), 2019 14th Iberian Conference on Information Systems and Technologies (CISTI) [8760794] (Iberian Conference on Information Systems and Technologies, CISTI; Vol. 2019-June). IEEE Computer Society. https://doi.org/10.23919/CISTI.2019.8760794